Quality of the Skill Skill Instrument Install Brick Based on the Indonesian National Qualification Framework (KKNI) - Muhammad Eko Prasetyo; Daryati Daryati; Riyan Arthur (Universitas Sarjanawiyata Tamansiswa, 2019)
In the development of the current world of construction, mastery of competencies is themost important thing that every artisan must have in carrying out his work. To measure thecompetence of the artisan, an instrument is needed. The instrument used can be used as a reference forevaluating competencies that are by the standards and conditions in the field which later can helpcreate artisan who is qualified and able to keep abreast of the developments that occur in the world ofconstruction today. This study aims to determine whether the existing brick installation workinstruments are by the standards and needs in the field. This study uses qualitative methods with datacollection techniques in the form of questionnaires aimed at experts to obtain expert recognition orjustification of existing instruments. From the results of the study, according to the expert justification,it was found that there were several items of masonry work that were rarely used and not includingcore work or more precisely the work was only done if there were orders from owners and valuationmethods that were considered less objective in assessing job competencies brick couple. The benefitsof this research can be a reference in developing brick installation work instruments.